Studi Keanekaragaman Bivalvia Pada Zona Intertidal Di Pantai Kota Pangkalpinang - Ramadhan Tritama; Irma Akhrianti; Mu’alimah Hudatwi (Journal of Tropical Marine Science, 2022)
The intertidal zone is an area that is located at the very edge of coastal and marine ecosystems and borders on land ecosystems. It is feared that continuous and environmentally unfriendly fishing will have an impact on the sustainability of bivalves. This research was conducted from February 2021 which aims to determine the diversity of bivalves and the relationship between diversity and environmental parameters. Bivalves data retrieval using a systematic random method consisting of live bivalves and dead shells. Data retrieval is divided into 4 stations, where each station consists of 3 substations. The results obtained 8 species of bivalves that are still alive from 3 families and a total of 143 individuals. Dead shells were obtained by 9 species from 7 families. The highest bivalves density was at station 1, which was 6.21 individual/m2, while the lowest was at station 3, which was 2.44 individual/m2. The highest bivalves diversity was found at station 2 with an H value of 2,05 and the lowest was at station 3 with a value of H'1,66. The index of bivalves diversity on the coast of Pangkalpinang City was in the moderate category due to excessive ecological pressure that could reduce the abundance of organisms and disturb the balance of the ecosystem. The results of principal component analysis (PCA) showed that the density of bivalves was positively correlated with clay, BOT, and TSS. While the diversity of bivalves is influenced by temperature, pH, and salinity.